1979
DOI: 10.1002/jcp.1040990113
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of wheat germ agglutininbinding sites on surfaces of chick embryo cells during early differentiation

Abstract: The objective of this work was to examine changes in a surface component of cells from the chick embryo during morphogenetic migrations of gastrulation. Two electron microscope techniques were used to localize cell-bound wheat germ agglutinin (WGA), a lectin which specifically binds N-acetyl glucosamine residues. One technique involved conjugation of peroxidase to WGA before reaction with the cells; the other technique used glucose oxidase to mark WGA which was already cell-bound. In both cases, binding was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Previous authors have shown that carbohydrate moieties of glycoconjugates found at the surface of cells undergo structural modification during embryonic development (Mayli& Pfenninger and Jamieson 1980;Huck and Hatten 1981;Blanks and Johnson 1983;Fazel et al 1989). With regard to the relationship between the change of sugar residues and cell differentiation, evidence strongly suggests that lectin-binding changes occur concomitantly with differentiation of embryonic cells in sea urchins (Krach et al 1974), in chick blastoderms (Zalik and Cook 1976;Sanders and Anderson 1979), in quail neural crest cells in vitro (Sieber-Blum and Cohen 1978) and in rat neurons (Pfenninger and Mayli&Pfenninger 1979). The present study also demonstrated that there was a masking effect, i.e., anti-recognition of sialic acid, of binding sites for Con A, PNA and SBA, which had a Ordinate : the average ranking of the intensity of fluorescence from 5 embryos in each group (15 total specimens).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have shown that carbohydrate moieties of glycoconjugates found at the surface of cells undergo structural modification during embryonic development (Mayli& Pfenninger and Jamieson 1980;Huck and Hatten 1981;Blanks and Johnson 1983;Fazel et al 1989). With regard to the relationship between the change of sugar residues and cell differentiation, evidence strongly suggests that lectin-binding changes occur concomitantly with differentiation of embryonic cells in sea urchins (Krach et al 1974), in chick blastoderms (Zalik and Cook 1976;Sanders and Anderson 1979), in quail neural crest cells in vitro (Sieber-Blum and Cohen 1978) and in rat neurons (Pfenninger and Mayli&Pfenninger 1979). The present study also demonstrated that there was a masking effect, i.e., anti-recognition of sialic acid, of binding sites for Con A, PNA and SBA, which had a Ordinate : the average ranking of the intensity of fluorescence from 5 embryos in each group (15 total specimens).…”
Section: Discussionmentioning
confidence: 99%
“…Thorpe et al (1988) and Loveless et al (1990) have shown how the binding sites for certain carbohydrate antibodies may be masked by sialic acid. However, less information regarding sialic acid masking of lectin-binding sites on the developing ectoderm can be found (Zalik and Cook 1976;Sanders and Anderson 1979;Slack 1985). Con A is a lectin with a broad spectrum type of specificity (Watanabe et al 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con A and WGA have been ultrastructurally localized during gastrulation previously ( Hook and Sanders, 1977;Sanders and Anderson, 1979). In the case of RCA the binding was highly localized.…”
Section: Electron Microscopymentioning
confidence: 95%
“…Lectin cytochemistry has been used extensively for this purpose in many developmental studies (reviewed by Sanders, 1986b;Damjanov, 19871, not only in the early chick embryo (Hook and Sanders, 1977;Sanders and Anderson, 1979;Takahashi and Howes, 1986;Griffith and Wiley, 19901, but also in the amphibian (Nosek, 1978) and the mammal (Currie et al, 1984;Smits-van Prooije et al, 1986;Griffith and Wiley, 1989). In the present study, we have used an extensive panel of lectins, at the light and electron microscope levels, to characterize cell surface changes in the chick embryo during gastrulation and neurulation.…”
mentioning
confidence: 99%